IDENTIFIKASI SERANGGA DAN FAKTOR ABIOTIK PERUSAK NASKAH KUNO SEBAGAI UPAYA PELESTARIAN BUDAYA PALEMBANG - Irham Falahudin (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2018)
The manuscript is one of the relics of the past owned by the people of Indonesia. The manuscript stored a number of past information that shows the thoughts, feelings, beliefs, customs, and values that apply to past societies. Manuscripts are available in various regions in Indonesia, one of them in Palembang. Malay manuscripts are texts written in Malay which are generally Arabic-Malay (Jawi). The existence of this ancient manuscript located in vulnerable society will be damaged . The importance of biological knowledge to this text makes provision for society and government in an effort to keep the extinct. Objectives of the research are to know the form and type of destruction of manuscripts, factors causing damage, to identify the types of biota and insects that destroyed and also how to cope with the presence of insects and biota in Malay manuscript storage. The research with a descriptive quantitative approach. The sampling of insects and biota by hand collecting method. Identified insect use to morphometric technique. The results are found 11 species of insects from 5 orders and 6 families. Cause damage to manuscripts in Palembang include as physical and chemical factors. Processes causing the destruction of manuscripts include biological factors Keyword: Identification Insect and abiotic factors, Manuscript Malay in Palembang